Bugonia [videorecording (DVD)] - Tracy, Will, 1983-; Stone, Emma, 1988-; Plemons, Jesse, 1988-; Delbis, Aidan; Halkias, Stavros, 1989-; Silverstone, Alicia; Ryan, Robbie; Johnson, Jennifer (Costume designer); Fendrix, Jerskin; Chang, Chun-hwan (Universal Studios, 2025)
Two conspiracy obsessed young men kidnap the high-powered CEO of a major company, convinced that she is an alien intent on destroying planet Earth.